2014
DOI: 10.1016/j.neuron.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Novel Primate miRNAs Coevolved with Ancient Target Genes in Germinal Zone-Specific Expression Patterns

Abstract: Summary Major non primate-primate differences in corticogenesis include the dimensions, precursor lineages and developmental timing of the germinal zones (GZ). microRNAs (miRNAs) of laser dissected GZ compartments and cortical plate (CP) from embryonic E80 macaque visual cortex were deep sequenced. The CP and the GZ including Ventricular Zone (VZ), outer and inner subcompartments of the Outer SubVentricular Zone (OSVZ) in area 17 displayed unique miRNA profiles. miRNAs present in primate, but absent in rodent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 51 publications
(69 reference statements)
4
69
0
Order By: Relevance
“…Corticogenesis in primates differs from that in non-primates in a number of ways, including the extent of cortical expansion, the identity of precursor lineages, and the emergence of neurogenic niches, so-called germinal zones (GZs) (Dehay et al, 2015). A recent study (Arcila et al, 2014) analyzed and compared miRNA expression profiles of a laser-dissected GZ (divided into an internal and external outer subventricular zone, the latter of which is specific for primates) and the cortical plate of the macaque visual cortex at embryonic day 80. Intriguingly, this analysis revealed that primatespecific miRNAs are amongst the most differentially regulated miRNAs between the regions analyzed (Arcila et al, 2014).…”
Section: Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Corticogenesis in primates differs from that in non-primates in a number of ways, including the extent of cortical expansion, the identity of precursor lineages, and the emergence of neurogenic niches, so-called germinal zones (GZs) (Dehay et al, 2015). A recent study (Arcila et al, 2014) analyzed and compared miRNA expression profiles of a laser-dissected GZ (divided into an internal and external outer subventricular zone, the latter of which is specific for primates) and the cortical plate of the macaque visual cortex at embryonic day 80. Intriguingly, this analysis revealed that primatespecific miRNAs are amongst the most differentially regulated miRNAs between the regions analyzed (Arcila et al, 2014).…”
Section: Neurogenesismentioning
confidence: 99%
“…A recent study (Arcila et al, 2014) analyzed and compared miRNA expression profiles of a laser-dissected GZ (divided into an internal and external outer subventricular zone, the latter of which is specific for primates) and the cortical plate of the macaque visual cortex at embryonic day 80. Intriguingly, this analysis revealed that primatespecific miRNAs are amongst the most differentially regulated miRNAs between the regions analyzed (Arcila et al, 2014). This finding implies that newly evolved miRNAs could contribute to the emergence of primate-specific cortical features and could be involved in higher cognitive functions unique to primates.…”
Section: Neurogenesismentioning
confidence: 99%
“…Notably, miRNAs present in primate, but absent in rodent, contributed vastly to differential gene expression between neocortical germinal zones of fetal macaque neocortex [76 ]. Regulators of cell cycle and neurogenesis were enriched among the targets of these miRNAs.…”
Section: Micrornasmentioning
confidence: 99%
“…Recent studies have implicated primate-specific miRNAs in several important physiological processes. 23,26 Because GDF15 is a target of p53, we hypothesized that the embedded miR-3189 is also p53-responsive. Indeed, the pattern of pri-miR-3189 expression closely matched that of its host gene following p53 activation.…”
mentioning
confidence: 99%